Evaluation of Thyroid Diseases and Differentiated Thyroid Cancer in Acromegalic Patients - Dogan, Serkan; Atmaca, Aysegul; Dagdelen, Selcuk; Erbas, Belkis; Erbas, Tomris (Springer, 2014)
Thyroid diseases are frequently seen in patients with acromegaly. The aim of this study is to evaluate thyroid diseases and thyroid cancer in acromegalic patients followed in a single institution. The data of 92 acromegalic (43 male, 49 female) patients followed over 12 years were retrieved retrospectively from the hospital recordings. All available data for gender, age, body weight and height, duration of acromegaly, age at diagnosis of acromegaly, treatment methods for acromegaly and history of thyroid disease, serum GH, IGF-1, thyroid function tests, thyroid ultrasonography (US), thyroid scintigraphy and thyroid fine needle aspiration biopsy (FNAB) results were recorded for the patients. The mean age of the patients was 43.9 +/- 10.8 years and the mean disease duration was 12 +/- 6.9 years. Thyroid US was performed in 64 patients who had nodular or diffuse goiter on palpation during the post-treatment follow-up and nodules were found in 44 (47.8 %) patients. Final diagnosis in 64 patients with thyroid US results and thyroid function tests including 26 patients with FNAB were as follows: 31 (48.4 %) benign multinodular goiter (MNG), 6 (9.4 %) simple nodular goiter, 1 (1.6 %) toxic MNG, 1 (1.6 %) Hurthle cell adenoma, and 5 (7.8 %) differentiated thyroid cancer. In addition, 9 (14.1 %) patients had diffuse goiter. One of the patients with diffuse goiter had amiodarone induced thyrotoxicosis. Eleven (17.1 %) patients had normal thyroid US and no other thyroid disease. Patients with nodules had longer disease duration than patients without nodules (14.2 +/- 6.6 vs. 9.4 +/- 3.4 years, p = 0.043). Thyroid volume was positively correlated with post-treatment GH and post-treatment IGF-1 levels (r = 0.309, p = 0.041 and r = 0.423, p = 0.004), respectively. We found that 7.8 % of our acromegalic patients with thyroid US results were diagnosed with thyroid cancer. Therefore, acromegalic patients must be considered as a high risk group for the development of thyroid cancer and must be closely followed for thyroid nodules and tumors.
Keywords: Acromegaly; Thyroid Cancer; Thyroid Nodules; Growth Hormone; Insulin-Like Growth Factor-1